Curriculum Innovation in Reproducing Ulama Cadres: A Case Study at Ma'had Aly Iqna' Ath-Thalibin (MAIT) Sarang - Ahmad Nashiruddin; Raharjo; Ismail SM; Mas'ud; Nur Khosiin (UIN Sunan Gunung Djati Bandung, 2025)
The purpose of this research is to find the curriculum model of Ma'had Aly Iqna' Ath-Thalibin Sarang in the reproduction of ulama cadres, as well as to discover its implementation in learning. This research was conducted using a descriptive approach and a qualitative research design. The descriptive approach in the context of this research is used to seek and provide an overview of the form and implementation of the Ma'had 'Aly educational curriculum. This study employs several techniques, including non-participant observation, unstructured interviews, and documentation. Data validity tests were conducted using triangulation of techniques and sources. Data analysis was performed interactively and continuously until the data was completed, according to Miles and Huberman. The research results indicate that Ma'had Aly Iqna' Ath-Thalibin Sarang integrates courses that are distinctive or specific to its major namely tasawuf, based on the reference of the Minister of Religious Affairs Regulation (PMA) which requires several general subjects. This curriculum is implemented using two learning strategies. That is, in the form of face-to-face and non-face-to-face. In the face-to-face format, the methods used are bandongan, sorogan, and mudzakaroh. Meanwhile, the non-face-to-face format is realized in the form of bahtsul masail, assignments, both individually and in groups. Overall, the implementation and evaluation framework at MAIT Sarang demonstrate a balanced approach between traditional Islamic pedagogy and modern academic standards, aiming to produce ulama who are intellectually competent, spiritually grounded, and socially responsible.